Investigation on the fracture toughness of a low-density δ-quenching and partitioning steel sheet - Z.L. Li; D.D. Cui; Y.S. Zhang; D. Chen; L. Gao; X.Q. Wang; X.W. Li (Journal of Materials Research and Technology)
The low-density δ-quenching and partitioning (δ-QP) steels have been developed, showcasing excellent strength and ductility. However, studies on the fracture toughness related to practical applications still remain relatively scarce. In this work, the fracture toughness of 1180 MPa grade δ-QP steels was investigated using double edge notched tension (DENT) tests. The tempering treatment at 350 °C promotes carbon partitioning from martensite to austenite and ferrite, enhancing microstructural uniformity and reducing stress concentration, which significantly improve the fracture toughness of the QP1180 sample. In contrast, higher annealing temperatures for the QP1280 sample bring about a lower fraction of austenite at the final microstructure and consequently a reduced microstructural uniformity, and there also exists a greater hardness difference between martensite/austenite islands and ferrite; therefore, a lower fracture toughness is obtained compared to the QP1180 sample. On the whole, the QP1180 sample exhibits the highest fracture toughness across different ligament lengths, primarily due to its uniform microstructure and more remarkable transformation-induced plasticity effect. Finite element simulation further verifies the strain distribution characteristics during deformation. This study provides valuable insights into the fracture toughness and fracture mechanisms of low-density δ-QP steels; it is of significant importance for their practical applications.